Intelligent Wearable Occupational Health Safety Assurance System of Power Operation. - Xie, Xiaona; Chang, Zhengwei (Journal of Medical Systems, 2019)
To improve the capacity of emergency control over on-site operation risk and effectively guarantee safety of operators in a complicated environment, a wearable safety assurance system framework for power operation is proposed. The framework centres on a wearable information processing gateway for single man and provides standardized access for vital signs monitoring, human-machine interaction and other equipment in a form of wireless ad hoc network. Using wearable vital signs monitoring equipment, the physiological parameters such as heart rate, body temperature and blood pressure can be monitored in real time. By extracting physiological parameters and SVM machine learning method, the operator's health condition is judged. Practical application shows that the wearable safety assurance system can evaluate the life status of workers in complex environment in real time, and can detect the risk of personal safety accidents caused by abnormal physical condition in the process of operation in advance.